Systematic Literature Review: Ethnomathematical Context of Batik Motifs in Mathematics Learning - Roesdiana, Lessa; Juandi, Dadang; Turmudi, Turmudi (SJME (Supremum Journal of Mathematics Education), 2024)
This study aims to determine whether ethnomathematics of batik motifs can be used as a mathematics learning approach and implemented in schools. The results of identifying articles from 2013 to 2023 through systematic literature review (SLR) referring to the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) obtained 12 sinta articles from a database of 200 articles. The findings of the SLR are two types of articles that are implemented directly to students in schools and only examine ethnomathematics from various batik motifs, geometry transformation material obtained from all articles